Modelling route choice of Dutch cyclists using smartphone data - Bernardi, Silvia; La Paix-Puello, Lissy; Geurs, Karst (Journal of Transport and Land Use, 2018)
This paper analyzes the GPS traces recorded by cyclists in the framework of the Mobile Mobility Panel throughout the Netherlands. The objective of this paper is to analyze bicycle route choice via network attributes and trip length over a sequence of trips by approximately 280 bicycle users, who were asked to register their trips by means of a specific smartphone application. Approximately 3,500 bike trips were recorded throughout the Netherlands over a four-week period in 2014. The bike trips have been matched to a specific bicycle network built and updated by a Dutch cyclists’ union. Route choice models were estimated, using both the binomial logit model and the mixed multinomial logit model with Path-size logit model formulation. The chosen alternatives were part of the choice set for the mixed multinomial logit model. Also, the shortest route was generated for each origin-destination pair. The results show that trip lengths and trip distribution over time reveal a population sample much used to cycling, frequently and over long distances. Furthermore, when considering the composition of chosen routes in terms of link type, the usage of cycleway links is frequent. For repeated trips, the shortest route option tends to be chosen more; frequent cyclists, on systematic trips, tend to optimize their trip and prefer the shortest routes. This is even truer for males and for non-leisure trips. The estimated probabilities for both multinomial and binomial models show that the binomial model tends to overestimate the probabilities of choosing the shortest route. This result is stronger in non-leisure trips, where people tend to choose a more personalized route, instead of the shortest. This research contributes to the generation of a more efficient distribution of bicycle trips over the network. Future research can more specifically address the intrapersonal variation in route—destination choice given the availability of longitudinal data.